2023
DOI: 10.1111/jdv.19222
|View full text |Cite
|
Sign up to set email alerts
|

Key factors predicting the in‐hospital mortality of patients with severe cutaneous adverse reactions in Thailand

Abstract: BackgroundAt present, no predictive models are available to determine the probability of in‐hospital mortality rates (HMRs) in all phenotypes of severe cutaneous adverse reactions (SCARs).ObjectivesOur study explored whether simple clinical and laboratory assessments could help predict the HMRs in any phenotypes of SCAR patients.MethodsFactors influencing HMRs in 195 adults diagnosed with different SCAR phenotypes were identified, and their optimal cut‐offs were determined by Youden's index. Predictive equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…This finding suggests that neutrophils may have a role in the early phase of the disease 47 . In line with this data, a prior study revealed a significant association between a high neutrophil-to-lymphocyte ratio and increased mortality in SJS/TEN 48 , 49 . In this present study, we demonstrated a significant correlation between serum MPO levels and the extent of epidermal necrosis in SJS/TEN.…”
Section: Discussionsupporting
confidence: 83%
“…This finding suggests that neutrophils may have a role in the early phase of the disease 47 . In line with this data, a prior study revealed a significant association between a high neutrophil-to-lymphocyte ratio and increased mortality in SJS/TEN 48 , 49 . In this present study, we demonstrated a significant correlation between serum MPO levels and the extent of epidermal necrosis in SJS/TEN.…”
Section: Discussionsupporting
confidence: 83%